2018
DOI: 10.1186/s12916-018-1021-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and behavioural and emotional comorbidity of acute seizures in young Kenyan children: a population-based study

Abstract: BackgroundAcute symptomatic seizures and febrile seizures are common in children admitted to hospitals in Africa and may be markers of brain dysfunction. They may be associated with behavioural and emotional problems, but there are no published community-based studies in Africa.MethodsWe screened 7047 children aged 1–6 years (randomly sampled from 50,000 in the community) for seizures (using seven questions) and invited those who screened positive and a proportion of negatives for a clinical assessment. Risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Infections were common. Studies from Kilifi identified falciparum malaria as the primary diagnosis in up to 65.4% children with acute symptomatic seizures,5,6,1521 while respiratory tract infections were the primary diagnosis in up to 27.8%5,6,22 and any infection identified in 80% of children with acute symptomatic seizures 5,6,15. Five percent of children admitted to hospital with acute symptomatic seizures hadepilepsy,14 a significant association (HR 1.53, 95% CI 1.10–2.14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infections were common. Studies from Kilifi identified falciparum malaria as the primary diagnosis in up to 65.4% children with acute symptomatic seizures,5,6,1521 while respiratory tract infections were the primary diagnosis in up to 27.8%5,6,22 and any infection identified in 80% of children with acute symptomatic seizures 5,6,15. Five percent of children admitted to hospital with acute symptomatic seizures hadepilepsy,14 a significant association (HR 1.53, 95% CI 1.10–2.14).…”
Section: Resultsmentioning
confidence: 99%
“…In a retrospective review of 6,639 pediatric EEGs performed for suspected epilepsy and reviewed at Kenyatta National Tertiary Referral Hospital, 3 Hz spike-wave activity, a feature of childhood absence epilepsy, was seen in 7.4% (163 of 2,216) of abnormal EEGs and hypsarrhythmia, seen with infantile spasms, in 2.8% (62 of 2,216) of abnormal EEGs 23. One Kilifi study6 assessed children presenting with acute seizures and found complex (focal, prolonged, or recurrent) seizures in 84%, generalized seizures in 85%, and EEG abnormalities in 27%. Another reported convulsive status epilepticus in 35.4% children with acute seizures 13…”
Section: Resultsmentioning
confidence: 99%
“…The 2001 Neurological Impairment Survey was conducted when malaria transmission was high 13,14 and the reduced prevalence of epilepsy may be attributed to a decline in seizures attributable to malaria and meningitis, which subsequently increased the risk for epilepsy 15,16 . The decline in the prevalence of epilepsy may also be attributed to sensitizations and prompt management of acute seizures, which reduced the risk of subsequent unprovoked seizures 28 …”
Section: Discussionmentioning
confidence: 99%
“…The high proportion of non-convulsive seizures may indicate childhood absence epilepsy or temporal lobe epilepsy are common in this area [30]. Temporal lobe epilepsy syndromes may be a consequence of acute seizures, malaria-associated seizures or status epilepticus, which are common in this area [31].…”
Section: Discussionmentioning
confidence: 99%